‘Connecting the dots’ for generating a momentum for Universal Health Coverage in Bangladesh: Findings from a cross-sectional descriptive study - Ahmed, Syed Masud; Rawal, Lal B; Naher, Nahitun; Hossain, Tarek (BMJ Journals, 2022)
This article was published in BMJ Open [© Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2018-024509 The Journal's website is at: https://bmjopen.bmj.com/content/9/7/e024509